Sex differences in pharmacotherapy and long-term outcomes in patients with ischaemic heart disease and left ventricular dysfunction. (25th November 2020) - Dagan, M; Dinh, D; Stehli, J; Tan, C; Brennan, A; Ajani, A.E; Freeman, M; Reid, C.M; Hiew, C; Oqueli, E; Kaye, D.M; Clark, D.J; et al.
Abstract: Background: Left ventricular dysfunction and ischaemic heart disease are common amongst women, however, women tend to present later and are less likely to receive guideline-directed medical therapy compared to their male counterparts. Purpose: To investigate if a sex discrepancy exists for optimal medical therapy (OMT) and long-term mortality in a cohort of patients with known ischaemic heart disease (IHD) and left ventricular dysfunction. Methods: We analysed prospectively collected data from a multicentre registry database collected between 2005–2018 on pharmacotherapy 30-days post percutaneous coronary intervention (PCI) in 13, 015 patients with left ventricular ejection fraction (LVEF) <50%. OMT at 30-days was defined as beta-blocker (BB), angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (ACEi/ARB) ± mineralocorticoid receptor antagonist (MRA). Long-term mortality was determined by linkage with the National Death Index, with median follow up of 4.7 (IQR 2.0–8.6) years. Results: Mean age was 65±12 years; women represented 20.2% (2, 634) of the cohort. Women were on average 5 years older, had higher average BMI, higher rates of hypertension, diabetes, renal dysfunction, prior stroke and rheumatoid arthritis. Men were more likely to have sleep apnoea, be current/ex-smokers and to have had prior myocardial infarction, PCI and bypass surgery. Overall, 72.3% (9, 411) of patients were on OMT, which was similar between sexes (72.7% in women vs. 72.2% in men, p=0.58). Rates of BB therapy were similar between sexes (85.2% vs. 84.5%, p=0.38), while women were less likely to be on an ACEi/ARB (80.4% vs. 82.4%, p=0.02) and more likely to be on a MRA (12.1% vs. 10.0%, p=0.003). Amongst those with LVEF ≤35% (n=1, 652), BB (88.7% vs. 87.3%, p=0.46), ACEi/ARB (83.3% vs. 82.1%, p=0.59) and MRA use (32.5% vs. 33.3%, p=0.78) was comparable. Aspirin use was similar between sexes (95.3% vs. 95.9%, p=0.12), while women were less likely to be on statin therapy (93.5% vs. 95.3%, p<0.001) and a second antiplatelet agent (94.4% vs. 95.6%, p=0.007). On unadjusted analysis women had significantly higher long-term mortality of 25.4% compared to 19.0% for men (p<0.001). Kaplan-Meier analysis out to 14 years demonstrated that men on OMT have the best long-term survival overall and women on sub-OMT have significantly poorer outcomes compared to men on sub-OMT. However, after adjusting for OMT and other comorbidities there was no difference in long-term mortality between sexes (HR 0.99, 95% CI 0.87–1.14, p=0.94). Conclusion: From this large multicentre registry, we found similar rates of guideline-directed pharmacotherapy for left ventricular dysfunction between sexes, however women were less likely to be on appropriate IHD secondary prevention. The increased unadjusted long-term mortality amongst women is likely due to differing baseline risk, given that adjusted mortality was similar between sexes. Funding Acknowledgement: Type of funding source: None